2012
DOI: 10.1111/j.1477-9552.2012.00355.x
|View full text |Cite
|
Sign up to set email alerts
|

Structural Change of European Dairy Farms – A Cross‐Regional Analysis

Abstract: Previous analyses of dairy farm structural change focus on the variation over time in one or a small number of regions. We present an EU-15 cross-regional analysis of the development of dairy farm numbers in different size classes over the period 1995-2005. Our purpose is to measure the explanatory relevance and effect of key factors suggested in the theoretical and empirical literature on structural change. Apart from the unprecedented scope, the underlying Markov chain analysis also contributes by combining … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
46
2
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(56 citation statements)
references
References 27 publications
(119 reference statements)
7
46
2
1
Order By: Relevance
“…The expected result that under milk quota restriction the growth of herd size would be negatively impacted by milk production per cow is only confirmed for medium farms' class. Another European Markov chain analysis which confirms this result is that of Zimmermann and Heckelei () who found that the elasticities for changes to larger size classes are, mostly, positively affected by milk yield, even under quota restriction, in most European regions. This could be explained by the fact that for large farms, under better productivity per cow and quota restriction, they have to either increase in size and increase their quota or exit.…”
Section: Resultssupporting
confidence: 60%
“…The expected result that under milk quota restriction the growth of herd size would be negatively impacted by milk production per cow is only confirmed for medium farms' class. Another European Markov chain analysis which confirms this result is that of Zimmermann and Heckelei () who found that the elasticities for changes to larger size classes are, mostly, positively affected by milk yield, even under quota restriction, in most European regions. This could be explained by the fact that for large farms, under better productivity per cow and quota restriction, they have to either increase in size and increase their quota or exit.…”
Section: Resultssupporting
confidence: 60%
“…The mainstream of research using nonparametric methods to assess the efficiency of agricultural production includes studies such as (Baran, 2009), which focuses on the efficiency of dairy cooperatives in Poland. Other examples include (Burja, 2011), a study focusing on Romanian agriculture; (Zimmermann and Heckelei, 2012), a report on European dairy farms; (Akande, 2012), an analysis of FADN regions; and (Atici, 2012), an article on Turkish agriculture. Moreover, (Baležentis and Valkauskas, 2013) examines the efficiency of selected farms in Lithuania; (Brummer and Thiele, 1999) looks at ways of studying aggregated efficiency on the basis of data on German farms; (Buckley and Carney, 2013) focuses on the analysis of efficiency in Irish agriculture; (Błażejczyk-Majka et al, 2011Špička, 2014) look at FADN regions; and (Smędzik, 2010) focuses on Polish farms.…”
Section: Introductionmentioning
confidence: 99%
“…Existing research on the influence of milk quotas includes the impact on changes in farm size (Breustedt and Glauben, 2007;Huettel and Jongeneel, 2011;Zimmermann and Heckelei, 2012), production (Ooms and Peerlings, 2005;Breustedt and Glauben, 2007;Huettel and Jongeneel, 2011), farm characteristics (Gale, 2003;Ooms and Peerlings, 2005;Huettel and Jongeneel, 2011), market conditions, land mobility (Harrington, 1995) or a combination of them (Zimmermann and Heckelei, 2012). However, all these studies focus on the impact of milk quotas, but not on the time at which they occur.…”
Section: Introductionmentioning
confidence: 99%